Synthesis Strategies and Multi-field Applications of Nanoscale High-Entropy Alloys - Zhang, Bin; Mu, Qingxue; Pei, Ye; Hu, Siyu; Liu, Shuo; Sun, Taolei; Gao, Guanbin (Nano-Micro Letters, 2025)
Alloying strategies have proven effective in enhancing the properties of metallic materials. However, conventional alloying strategies face significant limitations in preparing nanoscale multi-alloys and continuous optimizing surface-active sites. High-entropy alloys (HEAs) display a broader spectrum of unique properties due to their complex electron distribution and atomic-level heterogeneity arising from the stochastic mixing of multiple elements, which provides a diverse array of binding sites and almost continuous distribution of binding energies. This review aims to summarize recent research advancements in synthesis strategies and multi-field applications of nanoscale HEAs. It emphasizes several commonly employed synthesis strategies and significant challenges in synthesizing nanoscale HEAs. Finally, we present a comprehensive analysis of the advantages of HEAs for multi-field applications, emphasizing significant application trends related to nanosizing and multidimensionalization to develop more efficient nanoscale HEAs. Highlights: 1 The comprehensive overview of the synthesis of nanoscale high-entropy alloys and the advantages over conventional alloys. 2 The comprehensive overview of the multi-field applications of nanoscale high-entropy alloys and recent cutting-edge research advances. 3 The comprehensively analyses of the challenges and opportunities in high-entropy alloy development and emphasizes the key application trends in nanosizing and multidimensionalization.